A case-control study to identify risk factors for the occurrence of highly pathogenic avian influenza H5N1 in Nigeria - Métras, Raphaëlle; Stevens, Kim B.; Abdu, P.; Costard, Solenne; Okike, Iheanacho; Grace, Delia; Pfeiffer, Dirk U.; Randolph, Thomas F. (International Livestock Research Institute, 2009)
Since the first reported outbreak of highly pathogenic avian influenza (HPAI) H5N1 in Nigeria in 2006, there have been approximately 300 reported cases as at the end of August 2008, of which more than half occurred on backyard commercial farms. A case-control study was conducted in the two states of Kano and Lagos in Nigeria to identify risk factors for the occurrence of HPAI H5N1 outbreaks. Case and control farms were randomly selected from two lists provided by local authorities for the selected states. The list of case farms included farms having reported officially an HPAI H5N1 outbreak confirmed by the laboratory, during the outbreak waves 2006/7. The list of control farms included farms not having experienced any HPAI-like outbreak in 2006/7. A total of 110 farms (55 cases) were selected for the study; 64 in Kano and 46 in Lagos. Data were collected for each farm via a questionnaire and included farm characteristics, on-farm biosecurity, marketing practices and movement of people. A logistic regression model was used to identify factors associated with HPAI H5N1 outbreak occurrence. The results showed that farms not allowing traders to enter the premises had 0.1 the odds (95% CI [0.02 - 0.45]) of experiencing an outbreak compared with farms where traders entered poultry premises. Farms for which staff reported to wash their hands before handling birds had a significantly decreased odds of having an outbreak (OR=0.14, 95% CI [0.04 - 0.47]). Finally, it was shown that those farms sharing a fence with another poultry farm had 9.73 (95%CI [1.41 - 67.27]) the odds of experiencing an outbreak compared with farms not sharing a fence with another poultry farms. The results of this study highlight the importance of biosecurity measures in preventing HPAI H5N1 outbreaks in poultry farms in Nigeria. Government control measures have so far focused on stamping out, enhanced communication and advocacy, surveillance, capacity building and improved biosecurity in live-bird markets. The results of this study can be used to develop recommendations that could be applied by farmers on a daily basis at farm-level, such as restricting poultry premise access for traders, and having poultry-proof fences.